The wolves of winter : a novel - Johnson, Tyrell (Scribner, 2018)
"A captivating tale of humanity pushed beyond its breaking point, of family and bonds of love forged when everything is lost, and of a heroic young woman who crosses a frozen landscape to find her destiny. This debut novel is written in a post-apocalyptic tradition that spans The Hunger Games and Station Eleven but blazes its own distinctive path. Forget the old days. Forget summer. Forget warmth. Forget anything that doesn't help you survive in the endless white wilderness beyond the edges of a fallen world. Lynn McBride has learned much since society collapsed in the face of nuclear war and the relentless spread of disease. As the memories of her old life continue to haunt, she's forced to forge ahead in the snow-drifted Canadian Yukon, learning how to hunt and trap and slaughter. Shadows of the world before have found her tiny community--most prominently in the enigmatic figure of Jax, who brings with him dark secrets of the past and sets in motion a chain of events that will call Lynn to a role she never imagined. Simultaneously a heartbreakingly sympathetic portrait of a young woman searching for the answer to who she is meant to be and a frightening vision of a merciless new world in which desperation rules, The Wolves of Winter is enveloping, propulsive, and poignant"--